Development and evaluation of an insulator pollution monitoring apparatus - Potgieter, O. C. T.(Ockert Cornelius Theodoris) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1991.